Types of Maxim in Moana Movie - Siska Damayanti; Mhd. Johan (Humanitatis : Journal of Language and Literature, 2021)
Having a conversation is one way to get more information. When the speaker is talking to the listener, they must have context in it so that there is no misunderstanding between the speaker and the listener. To prevent misinterpretation between the speaker and the hearer, Grice proposes using the concept of cooperative values, which consists of a maxim, a simple assumption, and it can be modified. The purpose of this research is find out the type of maxim found in Moana movie. The researcher used qualitative descriptive to reveal the study, collecting the data and analyzing the data by using Pragmatics identity method. The result found that there are four maxims, namely maxims of quality, quantity, manner, and relevance in conversation of Moana movie. The researcher took 20 data from the script and found 8 maxim of quantity, 3 maxim of quality, 4 maxim of relation, and 5 maxim of manner in the script. It can be concluded that Moana did all cooperative principle in her utterances, but mostly, Moana used quantity maxim. It can be concluded that submissive of cooperative principle are mostly obeyed by character in Moana movie, so the result of communication is effective as required.